1992
DOI: 10.1002/j.1460-2075.1992.tb05050.x
|View full text |Cite
|
Sign up to set email alerts
|

Distamycin-induced inhibition of homeodomain-DNA complexes.

Abstract: The mobility shift assay was used to study the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 77 publications
(91 reference statements)
2
59
0
Order By: Relevance
“…A similar model has been suggested to explain the effect of distamycin A on the Antennapedia HD⅐DNA complex (52). Interestingly, it has already been proposed that distamycin A and HMGI DNA binding domains have a similar planar crescent-shaped structure and can compete for the binding in the minor groove of AT-rich sequences (16).…”
Section: Fig 4 Kinetics Of Hmgi-c Inhibitory Effect On Hd-cant1 Intmentioning
confidence: 56%
See 1 more Smart Citation
“…A similar model has been suggested to explain the effect of distamycin A on the Antennapedia HD⅐DNA complex (52). Interestingly, it has already been proposed that distamycin A and HMGI DNA binding domains have a similar planar crescent-shaped structure and can compete for the binding in the minor groove of AT-rich sequences (16).…”
Section: Fig 4 Kinetics Of Hmgi-c Inhibitory Effect On Hd-cant1 Intmentioning
confidence: 56%
“…Moreover, it has been demonstrated that, even at very high concentrations, this drug is not able to affect HDs/DNA interactions (52). Therefore, berenil should compete with HMGI-C for the minor groove interaction and reduce the inhibitory effect of this protein on HD binding to DNA.…”
Section: Hmgi Proteinsmentioning
confidence: 99%
“…For example, the A͞T-selective minor groove-binding agent distamycin prevented the TATA binding protein from binding to its A͞T-rich target site in the minor groove, but it was unable to inhibit the major groove-binding TF EGR from binding to its G͞C-rich sequence (2). However, distamycin could prevent major groove-binding homeodomain peptides from binding to their A͞T-rich sites (3).…”
mentioning
confidence: 99%
“…Failure to inhibit transcription in vivo could be caused by insufficient nuclear concentrations of the inhibitor or possibly by the presence of numerous competing TCCT sites in the eukaryotic genome. Recently, other minor groove binders have been studied for their effects on the transcriptional machinery (33,34 …”
Section: Discussionmentioning
confidence: 99%